Evaluation of Diagrams in Science Textbooks for Middle school in The Kingdom of Saudi Arabia - Al-Subaiee, Khulood Abdullah; Al-Raddadi, Samar Suleiman; Al-Ahmadi, Sawsan Nasser (Journal of Educational and Psychological Sciences, 2021)
The aim of the current research is to determine the extent to which the images, drawings and tables included in science textbooks for all middle school grades meet the textbooks standards, which are: (appropriateness of the shape's position to the concept, clarity and attractiveness of the colors, titles, size, realism, density of shapes, clarity, adequacy of number). To achieve the research goal the descriptive analytical approach was used, The research ppopulation consisted of all science textbooks for middle school (6) textbooks of the edition (2019). The results showed that the highest standard for images is: (titles) by (69%), and the highest standards for drawings are: (appropriateness of the shape's position to the concept, clarity and attractiveness of the colors, titles, density of shapes, clarity) by (40%), while the highest standard for tables is: (realism) by (16%).As for the least applicable standard in the images is (size) by (46%), and the least applicable standards in the drawings are (appropriateness of the shape's position to the concept, clarity and attractiveness of the colors) by (27%), and the least standards that applies to the tables are (clarity and attractiveness of the colors, and appropriateness of the shape's position to the concept) by (7%).In light of the results, it was recommended that attention should be paid to image standards (size, clarity and realism), as well as the need to pay attention to drawings standards (appropriateness of the shape's position to the concept, clarity and attractiveness of the colors, titles, density of shapes, clarity, and adequacy of number), as well as the need to pay attention to tables standards (appropriateness of the shape's position to the concept, clarity and attractiveness of the colors, titles, density of shapes, clarity, and adequacy of number) in science textbooks for the middle school.
Keywords: Science textbooks; Diagrams; Images; Drawings; Tables